Assembling an effective paediatric HIV treatment and prevention toolkit. - Cluver, L; Sherr, L; Grimwood, A; Richter, L; Phelps, B; Bachman, G; Desmond, C; Behnam, N; Fatti, G; Coovadia, H (Elsevier, 2014)
The world has woken up to the importance of antiretroviral treatment and HIV prevention for children and adolescents. There is a clear need to expand access to paediatric treatment and prevention by building clinical delivery mechanisms. But stand-alone clinical services are insufficient: uptake of antiretroviral therapy (ART) and adherence remain suboptimal, and adolescent HIV incidence remains high. To improve paediatric survival, several psychosocial and economic barriers to treatment and prevention must be overcome. Such barriers include depression and stigma, which inhibit treatment adherence; psychological and community barriers to the prevention of vertical transmission; and severe poverty and child abuse, which are risk factors for transactional sex in adolescent girls.